Endohelminths of some species of fishes from Lake Xochimilco, Mexico - María Lourdes García-López; Guadalupe Salguero-Vargas; Luis Garcia-Prieto; David Osorio-Sarabia; Gerardo Pérez-Ponce de León (Revista Mexicana de Biodiversidad)
The helminth fauna of 8 introduced and 1 native species (Chirostoma jordani) of freshwater fishes from Xochimilco Lake in southern México City, Mexico, is studied for the first time. Five species of fishes from the families Goodeidae, Atherinopsidae and Poeciliidae were positive to helminth infections. Their helminth fauna consists of 5 species of parasites, including 1 adult tapeworm (Schyzocotyle acheilognathi), 2 trematode metacercariae (Posthodiplostomum minimum and Tylodelphys aztecae), and 2 larval stages of nematodes (Contracaecum sp. and Eustrongylides sp.). Schyzocotyle acheilognathi is recorded for the first time in the poeciliid Pseudoxiphophorus jonesii. The metacercariae of P. minimum and T. aztecae are the species that reached the highest prevalence, mean intensity and mean abundance values among the analyzed fish. The goodeid G. atripinnis exhibited the richest helminth fauna, since this species was parasitized by 5 helminth species. We hypothesize that the low helminth species richness of the Xochimilco Lake ichthyofauna, compared to that found in other water bodies in Central Mexico, might be the result of the biotic and abiotic conditions of the lake which are influenced by the pollution levels in the area. An alternative explanation would be that 8 of the 9 species of fishes analyzed are introduced species into Xochimilco Lake, and have not been in the system long enough to allow other helminth species potentially available to become established.